Visitor Satisfaction and Loyalty: Evidence from Lake Linow, Indonesia - Dendi Paputungan; Gene Henfried Meyer Kapantow; Jane Sulinda Thambas; Gloria Sallogayang Kariwangan (Information Technology and Science (ITScience), 2026)
A key question in tourism research, especially in new destinations, is how visitor experiences affect their long-term behavior. This research investigates the influence of visitor satisfaction on destination loyalty within the context of Lake Linow, Indonesia—an emerging, increasingly favored tourist destination. A quantitative methodology was employed, using data collected from 303 visitors via on-site surveys. To find out how satisfaction and loyalty are related, Partial Least Squares Structural Equation Modeling (PLS-SEM) was used. The findings demonstrate a robust, statistically significant relationship between visitor satisfaction and destination loyalty (? = 0.835, p < 0.001), suggesting that visitors who report more favorable experiences are considerably more likely to return and endorse the destination. The model demonstrates considerable explanatory power, accounting for 69.7% of the variance in loyalty. These findings suggest that visitors tend to form loyalty intentions based on their overall experience evaluation rather than isolated attributes. This study contributes to the literature by providing empirical evidence from an emerging tourism context, where such relationships remain underexplored. From a practical point of view, the results show how important it is to consistently provide visitors with satisfying experiences to encourage repeat visits and positive word of mouth. This will help tourism destinations stay competitive in the long run.